Mean Air Flow Rate and Optimum Frequency - Nataraja NP (Journal of All India Institute of Speech and Hearing, 1970)
Optimum frequency  is considered to be the frequency at which maximum physio-acoustic economy  is  achieved. The purpose  of this study was to  find  out  the economy in the use of air flow at optimum frequency (as determined by an objective method  of locating  optimum frequency).The mean air flow  rate  at optimum and at frequencies higher and lower than the optimum frequency were measured using an expirograph.15 male and 15 female adults were asked to phonate vowel \a\ as long as possible keeping the frequency and intensity constant, into the expirograph. Thus the mean air flow rate at optimum, + 100  Hz  + 200  Hz  +  50  Hz and-50 Hz from the optimum were determined. The results show that the mean airflow rate at optimum frequency  was  significantly lower than at other frequency levels. Therefore it was  considered that there was maximum economy at optimum frequency,  as determined by this method,  in terms of use  of air for phonation.